The effect of addition of various elements on properties of NiTi-based shape memory alloys for biomedical application - Kok, Mediha; Ates, Gonca (Springer Heidelberg, 2017)
In biomedical applications, NiTi and NiTi-based alloys that show their shape memory effects at body temperature are preferred. In this study, the purpose is to produce NiTi and NiTi-based alloys with various chemical rates and electron concentrations and to examine their various physical properties. N45Ti55, Ni45Ti50Cr2.5Cu2.5, Ni48Ti51X (X = Mn, Sn, Co) alloys were produced in an arc melter furnace in this study. After the homogenization of these alloys, the martensitic phase transformation temperatures were determined with differential-scanner calorimeter. The transformation temperature was found to be below the 37 degrees C (body temperature) in Ni45Ti50Cr2.5Cu2.5, Ni48Ti51X (X = Mn, Co) alloys; and the transformation temperature of the N45Ti55, Ni48Ti51Sn alloys was found to be over 37 degrees C. Then, the micro and crystal structure analyses of the alloys were made, and it was determined that Ni45Ti50Cr2.5Cu2.5, Ni48Ti51X (X = Mn, Co) alloys, which were in austenite phase at room temperature, included B2 (NiTi) phase and Ti2Ni precipitation phase, and the alloys that were in the martensite phase at room temperature included B19(i) (NiTi) phase and Ti2Ni phase. The common phase in both alloy groups is the Ti2Ni phase, and this type of phase is generally seen in NiTi alloys that are rich in titanium (Ti-rich).
Keywords: Corrosion Behavior; Mechanical-Properties; Microstructure; Transformation; Al; Cu; Biocompatibility; Phase; Wires